Development of sustainable calcium silicate board: Utilization of different solid wastes | [Desarrollo de tableros de silicato de calcio sostenibles: utilización de diferentes residuos sólidos] - Hossain, S.K.S.; Roy, P.K. (Sociedad Espanola de Ceramica y Vidrio, 2019)
The present investigation aims to estimate the feasibility of using eggshell and rice husk ash (RHA) as ingredients to produce calcium silicate board (CSB). The solid-state route was used to prepare the calcium silicate (CS) powder through the mixing of heat treated RHA (∼93% SiO2) and calcined eggshells (∼99% CaO) at 1050 °C. CSB specimens were prepared at room temperature by simple curing process followed by mixing of different proportions of CS powder, ordinary portland cement (OPC) and unground rice husk ash (URHA). Several physicals, mechanical and thermal characterizations of the cured specimens were performed. The addition of OPC and URHA with CS were significantly influenced all the properties of CSB. The wastes derived CSB was exhibited low density (<1000 kg/m3), comparable bending strength (∼6 MPa) and low thermal conductivity (<0.153 W/m K). These properties suggest that the waste derived board may be used in the internal lining of building for insulation. © 2019 SECV.
Keywords: Calcium silicate board; Waste; Eggshell; Rice husk ash; Humidity effect